Reprint of: The impact of enterprise risk management on the marginal cost of reducing risk: Evidence from the insurance industry - Eckles, David L.; Hoyt, Robert E.; Miller, Steve M. (Journal of Banking & Finance, 2014)
We test the hypothesis that practicing enterprise risk management (ERM) reduces firms’ cost of reducing risk. Adoption of ERM represents a radical paradigm shift from the traditional method of managing risks individually to managing risks collectively allowing ERM-adopting firms to better recognize natural hedges, prioritize hedging activities towards the risks that contribute most to the total risk of the firm, and optimize the evaluation and selection of available hedging instruments. We hypothesize that these advantages allow ERM-adopting firms to produce greater risk reduction per dollar spent. Our hypothesis further predicts that, after implementing ERM, firms experience profit maximizing incentives to lower risk. Consistent with this hypothesis, we find that firms adopting ERM experience a reduction in stock return volatility. We also find that the reduction in return volatility for ERM-adopting firms becomes stronger over time. Further, we find that operating profits per unit of risk (ROA/return volatility) increase post ERM adoption.